Attitude towards collaborative care among nurses and physicians at a teaching hospital, Chitwan - Karki, Alisha; Thapa, Sara; Thulung, Bedantakala (Journal of Chitwan Medical College, 2018)
Interprofessional collaboration is recognized as a means of improving patient outcomes and the cost effectiveness of care in a variety of settings from primary health care to acute care to rehabilitation. Hence, health professionals must be able to work collaboratively in interprofessional teams or groups in order to ensure consistent, continuous, and reliable care. This study was conducted to identify attitude towards collaborative care among nurses and physicians. A descriptive cross sectional study design was adopted and a total 131 respondents were selected from different units of Chitwan Medical College Teaching Hospital by using probability stratified proportionate random sampling technique. A standardized tool (Jefferson Scale of attitude towards collaborative care among Nurses and Physician) was used to collect the data. Descriptive and inferential statistics was used to analyze data. Nearly half of the physicians (47.7%) and one quarter of the nurses (25.3%) had good attitude towards collaborative care. There is significant association between the level of attitude of physician and professional qualification (p=0.016) and designation of physicians (p=0.013). The hospital administration needs to focus establishing environment for health professionals’ to develop positive attitude toward collaborative care.